The Influence of Political Messages on User Engagement within Social Media Environments - Mariani, Ronda; Price, Fitzgerald L.; Gumbs, Janelle (Journal of Management Policy and Practice, 2019)
This study explores the predictors of user interactions in response to political messaging within the social media environment. Research exposes whether trust had a significant role in social media user’s engagement and identifies what factors determine user trust. Using a cross-sectional survey methodology, data was collected based on descriptive characteristics of survey respondents. Scales were also used to evaluate trust interpretations of political messages. Respondents overwhelmingly indicate that trust was a key consideration when engaging political messages on social media. Findings indicate a significant increase in the trust of political messages generated by Facebook and Twitter social media platforms.